Pengaruh Pemanfaatan Sistem Informasi Akuntansi dan Pengaruh Teknologi Informasi Terhadap Kinerja UMKM (Studi Kasus pada UMKM Kecamatan Lowokwaru, Kota Malang) - Putri, Yearsina Simanjari; Mahsuni, Abdul Wahid; Junaidi, Junaidi (Universitas Islam Malang, 2024)
This study aims to examine how MSMEs utilize accounting information systems and investigate the impact of the influence of information technology use on the performance of small and medium enterprises. This study seeks to understand the relationship between the implementation of technology solutions in the accounting process and the operational effectiveness of MSMEs. This research targets business actors who manage small and medium- sized businesses. The focus of this research is directed to MSME owners operating in the city of Malang the sample used consists of 97 respondents with predetermined criteria. This study uses a purposive sampling method with a quantitative approach. This study uses primary data collected directly from respondents. The results of this study show that accounting information systems have a positive influence on the performance of MSMEs (1) Information Technology has a positive influence on the performance of MSMEs (2).Keywords: Utilization of accounting information systems, Influence of information technology, MSME performance